2014
DOI: 10.1016/j.celrep.2013.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Assessing PIK3CA and PTEN in Early-Phase Trials with PI3K/AKT/mTOR Inhibitors

Abstract: Despite a wealth of preclinical studies, it is unclear whether PIK3CA or PTEN gene aberrations are actionable in the clinical setting. Of 1,656 patients with advanced, refractory cancers tested for PIK3CA or PTEN abnormalities, PIK3CA mutations were found in 9% (146/1,589), and PTEN loss and/or mutation in 13% (149/1,157). In multicovariable analysis, treatment with a PI3K/AKT/mTOR inhibitor was the only independent factor predicting response to therapy in individuals harboring a PIK3CA or PTEN aberration. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
194
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 219 publications
(208 citation statements)
references
References 44 publications
9
194
2
Order By: Relevance
“…Notwithstanding the fact that the TCGA Pan-Cancer study has focused exclusively on gene mutations, but not on gene amplification, the data are still conflicting with previous publications [47]. Nonetheless, ongoing clinical trials support the benefit of ovarian cancer patients from the pharmacological inhibition of the PI3K/AKT/mTOR pathway, therefore reinforcing the fact that solving ovarian cancer molecular profiling by means of characterizing the heterogeneity of its subtypes and their mutational landscape likely represents an opportunity to fight the disease using target therapies effective against specific aberrations [75][76][77].…”
Section: Ovarian Cancercontrasting
confidence: 49%
“…Notwithstanding the fact that the TCGA Pan-Cancer study has focused exclusively on gene mutations, but not on gene amplification, the data are still conflicting with previous publications [47]. Nonetheless, ongoing clinical trials support the benefit of ovarian cancer patients from the pharmacological inhibition of the PI3K/AKT/mTOR pathway, therefore reinforcing the fact that solving ovarian cancer molecular profiling by means of characterizing the heterogeneity of its subtypes and their mutational landscape likely represents an opportunity to fight the disease using target therapies effective against specific aberrations [75][76][77].…”
Section: Ovarian Cancercontrasting
confidence: 49%
“…The implication that combinations of matched therapy as opposed to monotherapy might have a stronger association with survival for patients with multiple molecular alterations (median ¼ 4 in our study), and that the number of alterations should be relevant to outcome should not be unexpected. Importantly in this regard, other studies have also suggested that patients treated with single-agent matched therapies had significantly lower responses rates than patients treated with combinations (41). Finally, overall, 87 of our 347 patients (25%) were matched to therapy on the basis of their genomic results.…”
Section: Discussionmentioning
confidence: 99%
“…Another perspective for this issue derives from studies showing that, in colorectal cancer patients, aberrations in the KRAS/BRAF axis often coexist with aberrations in the PI3K/AKT/mTOR axis (83)(84)(85), with each being a resistance pathway for the other (86,87). These co-mutations occur in other cancers as well, but not as frequently.…”
Section: Role Of the Pi3k/akt/mtor Axismentioning
confidence: 99%